FKEE Staff Publication System - Ismail , Muhammad Nur Din; Mahamad , Abd Kadir; Saon, Sharifah; Ahmadon, Mohd Anuaruddin; Yamaguchi, Shingo; Tuwoso, Tuwoso (Journal of Electronic Voltage and Application, 2020)
The propose of this project is a development of web-based and mobile application of FKEE staff publication on Android platform, in order to improve accessibility and performance of the system. Currently, Faculty of Electrical and Electronic Engineering (FKEE) have existing system of staff publication information; however it lacks information such as publication list in Scopus, H-index and citations. Therefore, the proposed system aims to have all this features that help the user to access the information of publication easily. This system is managed by admin, for the reasons of security and auditing. Thus, the admin can access the system and edit the information accordingly, while the end user can only search and view the information of publication. The system shows all the information of FKEE staff such as the position, email, and list of publication. To ensure the success of Android application system development, MIT App Inventor 2 is used. On the other hand, the local server must have internet connection with the assistant of Serveo platform for web-based system. Furthermore, the performance of developed system are analyzed using Pingdom for website and ImmuniWeb for Android application. As a conclusion, the system has been successfully developed and some other features can be added in the future for the advancement of the system.